Millennium BIM’s development strategy in Mozambique - Fernandes, Diogo Almeida (2015)
Millennium BIM is the largest banking institution in Mozambique and has been the market leader since 2000. Having rapidly grown in a context of increasing bancarization of the population and positive evolution of socioeconomic factors, the bank has been experiencing an overflow of customer on its traditional branches which results in the erosion of the quality of customer service. This case study presents an overview of Millennium BIM, its operations in Mozambique, and contextualizes the dynamics of being part of the Millennium BCP Group. Moreover, the case study presents the key features of the Mozambican economy and population, it describes the banking sector in detail and presents metrics that portray the operational strains lived at Millennium BIM’s branches suggesting innovative initiatives to help resolve such challenges. The purpose of this case is to give the information necessary so that the reader is able to make a decision about the initiative(s) the bank should pursue in the near future. For that, a specific order of questions is presented, starting by analyzing the population characteristics, a segmentation the customer base and analysis of the reasons for a potential fit between each segment and each banking channel in order to successfully understand and choose the right initiatives to resolve the strains in the mass market branches. The final choice will result in a careful decision of which investments are better from a cost/benefit perspective.